Kosher mafia - Hazan, David (Mad Cave Studios, 2024)
"In Cleveland, Ohio, in 1936, Howard Berkowicz, the bookkeeper for the Jewish Mob finds himself on the wrong end of an enforcer's gun when he tries to spur the Kosher Mafia into action against the rising tide of domestic Nazism in the German American Bund."--